2023
DOI: 10.3389/fonc.2023.1166796
|View full text |Cite
|
Sign up to set email alerts
|

Combining methylated SDC2 test in stool DNA, fecal immunochemical test, and tumor markers improves early detection of colorectal neoplasms

Tao Zeng,
Zhongchao Huang,
Xufa Yu
et al.

Abstract: ObjectiveTo explore the value of testing methylated SDC2 (SDC2) in stool DNA combined with fecal immunochemical test (FIT) and serum tumor markers (TM) for the early detection of colorectal neoplasms.MethodsA total of 533 patients, including 150 with CRC (67 with early-stage CRC), 23 with APL, 85 with non-advanced adenomas and general polyps, and 275 with benign lesions and healthy controls. SDC2 was detected by methylation-specific PCR, FIT (hemoglobin, Hb and transferrin, TF) was detected by immunoassay, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, there is limited information on the utility of measuring both m SDC2 and m SEPT9 in blood and, based on the considerable performance in stool, may be worthy targets. Interestingly, a recent study showed high sensitivity (97.3%) for the detection of advanced precancerous lesions and CRC when combining stool-derived m SDC2 , FIT, and serum-derived CEA ( 35 ).…”
Section: Candidate Methylation Markers For Colorectal Cancer Detectionmentioning
confidence: 99%
“…However, there is limited information on the utility of measuring both m SDC2 and m SEPT9 in blood and, based on the considerable performance in stool, may be worthy targets. Interestingly, a recent study showed high sensitivity (97.3%) for the detection of advanced precancerous lesions and CRC when combining stool-derived m SDC2 , FIT, and serum-derived CEA ( 35 ).…”
Section: Candidate Methylation Markers For Colorectal Cancer Detectionmentioning
confidence: 99%
“…Cellular senescence was demonstrated that was connected with CRC or changed of metabolic pathways to inhibit cancer progression(6).Senescent cells are characterized by need su cient energy like mitochondrial to synthesize various metabolish pathway (7).Recently studies have shown that Mitochondrial disorders have been discoved in varity tumor cells and have demonstrated various mitochondrial proteins as pathological mechanism part to play a important role(8).In support of this,To change the number of mitochondrial content and activity, can affect the growth of cell differentiation and toward oxidative phosphorylation in metabolism(8).The mitochondrial energy metabolism pathway can regulate stem cell functions through many mechanisms, including citrate cycle tca cycle,fatty acid metabolism , ketone body metabolism , glycolysis gluconeogenesis, oxidative phosphorylation (9).Mitochondrial dysfunction was demonstrated that was involved in cellular senescence,and may changed the metabolic pathways to favor carcinogenesis (10).Such as a high expression gene GAPDHs in the mitochondrial glycolytic pathway was associated with worse clinical outcome in stage III melanoma (10). Accumulating evidence has proven molecular testing can help to diagnose and intervent CRC, improve patient prognosis, reduce mortality, and lower the economic burden of disease on individuals (5,11). Hence, investigations into the metabolic aspects of mitochondrial are anticipated to offer valuable insights for prognostic predictions and optimization of treatment strategies for individuals with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…have high variability due to differences in storage and transportation temperature, transit time and exact collection methods between patients. Another common method is fecal occult blood test (FOBT) cards (29)(30)(31)(32)(33). In FOBT sampling fecal smears are collected at home on specialized sample cards designed to detect blood.…”
mentioning
confidence: 99%
“…Specialized solutions such as the Cologuard® can be used for non-invasive tests that analyze stool samples patients collect on a commercial kit with a preservative buffer. This test uses genetic sequencing to detect colorectal precancers but is not optimized for metabolomics (32)(33)(34). For the majority of stool-based tests (screening for blood in the stool, stool culturing for bacterial or viral infections diagnostics, ova and parasite exam, fat malabsorption assessment, etc.…”
mentioning
confidence: 99%